Respuestas

  • Usuario de Brainly
2013-04-18T21:40:12+02:00
1 - 8/3 x (-3/4) - {2 - [3/4 - 1 + 2/5 x (-10 + 15/4 - 1)]}

los numeros que estan tumbados (-8/3 y -3/4) se simplifican:

 

1 + 2 - {2 - [-1/4 + 2/5 x (-11 + 15/4)]}  =

 

3 - {2 - [-1/4 + 2/5 x (-29/4)  =

 

3 - {2 - [-1/4 + (-58/20)]}  =

 

3 - [2 - (-5/20 - 58/20)  =

 

3 - [2 - (-63/20)]  =

 

3 - (2 + 63/20)  =

 

3 - (40/20 + 63/20)  =

 

3 - (103/20)  =

 

60/20 -103/20  =

 

-43/20

 

La solución es -43/20. 

 

Un saludo y suerte